Responses of earthworm communities to crop residue management after inoculation of the earthworm Lumbricus terrestris (Linnaeus, 1758) - Frazão, Joana; Goede, Ron G.M. de; Salánki, Tamás E.; Brussaard, Lijbert; Faber, Jack H.; Hedde, Mickaël; Pulleman, Mirjam Margreet (Elsevier, 2019)
Earthworms are important for soil functioning in arable cropping systems and earthworm species differ in their response to soil tillage and crop residue management. Lumbricus terrestris (Linnaeus, 1758) are rare in intensively tilled arable fields. In two parallel field trials with either non-inversion (NIT) or conventional tillage (CT), we investigated the feasibility of inoculating L. terrestris under different crop residue management (amounts and placement). Simultaneously, we monitored the response of the existing earthworm communities to L. terrestris inoculation and to crop residue treatments in terms of earthworm density, species diversity and composition, ecological groups and functional diversity. L. terrestris densities were not affected by residue management. We were not able to infer effects of the inoculation on the existing earthworm communities since L. terrestris also colonized non-inoculated plots. In NIT and two years after trial establishment, the overall native earthworm density was 1.4 and 1.6 times higher, and the epigeic density 2.5 times higher, in treatments with highest residue application (S100) compared to 25% (S25) or no (S0) crop residues, respectively. Residue management did not affect earthworm species composition, nor the functional trait diversity and composition, except for an increase of the community weighted means of bifide typhlosolis in S0 compared to S100. In CT, however, crop residues did have a strong effect on species composition, ecological groups and functional traits. Without crop residues (S0), epigeic density was respectively 20 and 30% lower than with crop residues placed on the soil surface (S100) or incorporated (I100). Community composition was clearly affected by crop residues. Trait diversity was 2.6 to 3 times larger when crop residues were provided, irrespective of placement. Crop residues in CT also resulted in heavier earthworms and in a shift in the community towards species with a thicker epidermis and cuticle, a feather typhlosolis shape, and a higher average cocoon production rate. We conclude that earthworm communities under conventional tillage respond more strongly to the amount of crop residue than to its placement. Under non-inversion tillage, crop residue amounts affected earthworm communities, but to a smaller degree than under conventional tillage.